2015
DOI: 10.1120/jacmp.v16i6.5317
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and reducing dose received by cardiac devices for patients undergoing radiotherapy

Abstract: The objectives of this project are to quantify the dose reduction effect provided by a lead shield for patients with cardiac implantable electronic devices (CIED) during a clinically realistic radiation treatment on phantom and to provide a simple model of dose estimation to predict dose received by CIED in a wide range of situations. The shield used in this project is composed of a lead sheet wrapped in thermoplastic. Dose measurements were made with a plastic scintillation detector (PSD). The phantom was tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…An analysis for maximum doses received by CIEDs (located outside the beam) for all CTPs confirmed that they are all lower than the historical threshold dose of 2 Gy. As can be seen from As detailed by AAPM TG-203, 17 and other studies, 11,24,39 there is no safe dose threshold below which no CIED damage occurs.…”
Section: Similar Results Were Obtained In Repeated Experiments Withmentioning
confidence: 90%
“…An analysis for maximum doses received by CIEDs (located outside the beam) for all CTPs confirmed that they are all lower than the historical threshold dose of 2 Gy. As can be seen from As detailed by AAPM TG-203, 17 and other studies, 11,24,39 there is no safe dose threshold below which no CIED damage occurs.…”
Section: Similar Results Were Obtained In Repeated Experiments Withmentioning
confidence: 90%
“…In closing, the interpretation of the data by Bourgouin et al (1) is not well‐substantiated for the reasons presented in this letter, and the use of a thin sheet of lead on the CIED is not necessary since it will not prevent internal scatter dose to reach the device. However, it is best if a 5 mm tissue‐equivalent bolus is used to cover the CIED and in vivo dosimetry is implemented as part of the management policy for that category of patients (8) .…”
mentioning
confidence: 73%
“…I read with great interest the manuscript of Bourgouin et al, (1) describing methods to estimate and/or measure out‐of‐field doses to a cardiac implantable electronic device (CIED) for patients that undergo radiotherapy. This is a topic that deserves great attention in today's radiotherapy practice since a great number of cancer patients who will receive radiation have a pacemaker or implantable cardioverter‐defibrillator.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, Fig. 2 (2) should be seen as a demonstration that our dose estimation model can work in different situations, rather than a recommendation to use lead shielding. In our clinic, lead covered in thermoplastic was used because it is easy to manipulate and position on the patient, but we agree that other materials could be used to the same effect.…”
mentioning
confidence: 99%